Desecularising the state: religion and politics in India after independence - Mitra, Subrata Kumar (Comparative studies in society and history, 1991)
The relationship of religion and politics is continuously fascinating and elusive, not least because it is rarely posed in a direct way. In stable democracies, incidents which are rather out of the ordinary, such as publishing the Satanic Verses in the United Kingdom or sporting the Islamic headscarf in a French state school, might push the issue temporarily to the centre of the political arena until the categories of normal politics, such as class, region, language or ethnicity, incorporate it or contrive to edge it beyond public visibility. In developing countries, one is accustomed to the more salient presence of religion in the public sphere: for example, the broad sweep of an Islamic revolution in Iran, popular jihad in the Middle East, the militant Sikhs in the Punjab, or the battle for the birthplace of Rama in North India. However, the intelligentsia in these countries who speak with the authority of modern science and the modern state see these events, important as they are, as the expression of primordial sentiments, and indicative of the underdeveloped nature of the people concerned, rather than as the political expression of unresolved issues, ill concealed by the fabric of normal politics and not articulated by political institutions.
Elektronische Reproduktion der Druck-Ausgabe
Published online by Cambridge University Press: 03 June 2009
Gesehen am 15.06.2021